2018
DOI: 10.1016/j.cub.2018.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence Detection of Membrane Stretch and Extracellular pH by the Proton-Sensing Receptor OGR1 (GPR68)

Abstract: Highlights d OGR1 (aka GPR68) requires cell stretch and extracellular protons to activate d Cell stretch and extracellular acidosis synergistically promote OGR1 signaling d Cell-stretch-mediated actin polymerization is crucial for OGR1 activity d Actin depolymerization limits how long OGR1 stays responsive after cell stretch SUMMARYThe physical environment critically affects cell shape, proliferation, differentiation, and survival by exerting mechanical forces on cells. These forces are sensed and transduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 47 publications
1
58
0
Order By: Relevance
“…Cells were deformed using a custom‐built substrate stretching device (Figure ), delivering uniaxial strain to cells cultured on ultrathin (50–100 µm) polydimethylsiloxane substrates (Silex, UK), and allowing for simultaneous high‐resolution microscopy and electrophysiological recording previously used in cell‐stretching experiments aimed at discerning the response of cells to membrane stretch (Wei et al, ). F11 cells were seeded on deformable substrates at 5,000 cells/substrate to allow for cell proliferation during differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were deformed using a custom‐built substrate stretching device (Figure ), delivering uniaxial strain to cells cultured on ultrathin (50–100 µm) polydimethylsiloxane substrates (Silex, UK), and allowing for simultaneous high‐resolution microscopy and electrophysiological recording previously used in cell‐stretching experiments aimed at discerning the response of cells to membrane stretch (Wei et al, ). F11 cells were seeded on deformable substrates at 5,000 cells/substrate to allow for cell proliferation during differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its ability to sense protons (H + ), GPR68 was recently shown to be a mechanosensor of shear stress in human and mouse vascular endothelial cells [56] and of stretch in other cell types [57]. Mechanosensing of shear stress required the presence of H + while for mechanosensing of stretch, GPR68 was proposed to be a coincidence detector for membrane stretch and extracellular H + [56,57]. GPR68 KO mice have lower systolic blood pressure than WT mice but without altered diastolic pressure, mean arterial pressure, or heart rate.…”
Section: G Protein-coupled Receptor 68 (Gpr68/ogr1)mentioning
confidence: 99%
“…In Xenopus, v-atpase regulates pH in a regional manner to affect craniofacial morphogenesis (Adams et al, 2006;Vandenberg et al, 2011) . Notably, recent studies of GPR68 have shown that the receptor senses flow and stretch (Wei et al, 2018;Xu et al, 2018) . However, responses to both stimuli are dependent on mildly acidic conditions.…”
Section: Discussionmentioning
confidence: 99%